Analysis of changes in production technology detail - Nieoczym, Aleksander (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
The article presents an analysis of the cost of the handle mounting geared universal waste conveyor. It proposed two methods: welded components and bending the blank. Using your own designs calculated execution times and production costs. It has been shown that the solution to be economically element bent on a press brake. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)